REKACIPTA MITE PUTRI MAYANG SEBAGAI BENTUK PENGEMBANGAN SASTRA LISAN DAYAK MAANYAN DI KABUPATEN BARITO TIMUR - Linggua Sanjaya Usop; Indra Perdana; Paul Diman; Nirena Ade Christy; Lazarus Linarto; Agroy Gloria; Saputri Nakalelu (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The reinvention of Mite Putri Mayang as a form of development of Dayak Maanyan oral literature in East Barito Regency is a form of innovation to revive the meaning of each story in it through the form of a short story. This research aims to create the Putri Mayang myth as a form of developing Dayak Maanyan folklore in East Barito Regency through short story writing. The research method used is the Participatory Planning and Research (PPR) research method, data analysis is carried out in a qualitative descriptive manner, so that the presentation only takes the form of an explanation in the form of words. Data collection was carried out by determining the research object, the material object was the oral literature myth of Putri Mayang, while the formal object was Ruth Finnegan's oral literature theory. Search for data in two ways, namely literature and field. The results of research regarding the Putri Mayang myth of the Dayak Maanyan tribe in East Barito Regency, it can be concluded that this story reflects local leadership without highlighting the superiority of the Banjaran or the inferiority of the Kedayakan. Putri Mayang Sari's leadership focuses on people's welfare, food security, and the implementation of the traditional Dayak Maanyan government system. This mythical story also contains religiosity, social, political and economic values ​​in ritual practices, inter-religious tolerance, an inclusive government system, and an emphasis on food security in the Maanyan Dayak community. The process of recreating the short story Putri Mayang shows creative efforts in reinterpreting the myth. Even though there are variations in interpretation, some short stories are still tied to the setting and characters of the original myth. For example, "Parang Maya" carries regional values ​​while giving a contemporary touch. The creation of short stories is a refreshing form of creativity in the cultural heritage of the Dayak Maanyan people.